AN ETHICAL INVESTIGATION INTO THE PERFORMANCE APPRAISAL OF SECURITY AGENCIES IN THE MANAGEMENT OF CRIMES IN A DEMOCRATIC SOCIETY: NIGERIA AS A CASE STUDY - Micheal, Abada; Ifeoma, Okafor (PEOPLE: International Journal of Social Sciences, 2018)
The nature and character of Post-Colonial states in Africa has remained in a state of vague. This is because of the contradictions between the bequeathed functions of the state and the systematic arrangements of actualizing its fundamental objectives. It is based on this premise that the objective of study sets out to ethically assess the performances of Nigeria’s security agencies in the management of Nigeria’s security challenges between 1999 and 2017.The study is necessitated by the debate in theoretical literature on the relationship between democracy and security. It is against this backdrop that the study sets to ethically investigate whether the re-introduction of democratic rule in Nigeria in 1999 has enhanced the security of lives and property of Nigerian citizens between 1999 and 2017.Data for the study were gathered and analyzed using the descriptive method. The Marxist theory of post- colonial state formed the framework of its analysis. The finding of the study is that the re-introduction of civil rule in Nigeria has not enhanced the security of lives and properties of Nigerian citizens as expected. The study therefore recommends among other things the need for forensic training and future studies on the organization of Nigeria’s security intelligence to ethically assess the management and performances of the nation’s security out fits.